The effect of applying the training circuit model to increase agility in futsal extracurricular participants - Taradipa, Alfian; Lengkana, Anggi Setia; Saputra, Yudha Munajat (Indonesian Journal of Sport Management, 2024)
Sport is a place for humans to explore motion. To improve agility in futsal, researchers will apply a circuit training model, Which offers many positive changes in students. This study is because agility in extracurricular futsal participants at SDN Ambit is still lacking, and agility training is not good because players do not master futsal. This study aims to determine the effect of applying the training circuit model in increasing agility in extracurricular futsal participants of SDN Ambit. This study used a pre-experimental method with the "One Group Pretest-Posttest Design" design. The population of this study was extracurricular participants of SDN Ambit. The data analysis technique used by this study is a paired sample t-test. The results were obtained to determine the effect of applying the training circuit model in increasing agility in futsal extracurricular participants. Until this research, the number of 16 students from Situraja sub-district of SDN Ambit Ambit Village. This study is a population because the entire sample is the total population. The research instrument uses an Illinois run test. After the students were given the treatment given to the research subjects, which showed a value of t = -6.536 with a significance value of 0.001 < 0.05, if < 0.05, it can be concluded that H1 is accepted. The conclusion obtained is that there is a significant influence on the results of applying the training circuit model in increasing agility in doing futsal sports, using the training circuit model first.